An Evaluation of Probiotic Potential of Lactobacillus sp. from Milk of Domestic Animals and Commercial Available Probiotic Preparations in Prevention of Enteric Bacterial Infections - and S.A. Bhutada, D.H. Tambekar* (Recent Research in Science and Technology, 2010)
Probiotics are the health promoting viable microorganisms that exhibit a beneficial effect on the health of human being by improving the intestinal microbial balance. A total of 120 milk samples (40 each from buffalo, cow, and goat) were analyzed and 110 isolates were identified as Lactic Acid Bacteria (LAB). Out of these 11 isolates were identified as prominent probiotics, among them 3 isolates were excellent probiotics. These excellent probiotics were compared for their probiotic potential with commercial probiotic preparations such as Sporlac powder, LactoBacil plus, P-Biotics kid, Gastroline, Pre-Pro kid and standard probiotic bacterial strains L. plantarum (MTCC 2621) and L. rhamnosus (MTCC 1048). The isolated LAB exhibited excellent probiotic characteristics than commercial probiotic preparations and standard probiotic bacterial strains. Study suggested that use of these probiotic bacteria from milk of domestic animals can be help to prevent or control the intestinal infections and contributes health benefits to consumers.